A modified Sobol′ sensitivity analysis method for decision-making in environmental problems. (January 2016) - Ganji, Arman; Maier, Holger R.; Dandy, Graeme C.
Abstract: Sensitivity analysis is an important component of environmental modelling and in recent years, variance-based, global sensitivity analysis techniques, such as Sobol′, have been a preferred approach for achieving this. However, these techniques are generally only applicable to simulation models and not to models used to rank alternative options, such as multi-criteria decision analysis (MCDA) methods. In order to overcome this limitation, a modified Sobol′ method for MCDA (Sobol′-MCDA) is introduced in this paper. The method has the following features: (i) it enables the stability or robustness of the relative ranking of two alternatives to be assessed in the light of changes in assessment criteria and stakeholder preferences; and (ii) it enables the sensitivity of the ranking of two alternatives to changes in assessment criteria and stakeholder preferences to be assessed. The approach is demonstrated for a water resources case study from the literature consisting of seven alternatives and ten assessment criteria. Highlights: A novel Sobol′ sensitivity analysis method for MCDA is introduced. The method provides a measure of the robustness of the ranking of an alternative. The method evaluates the sensitivity of the ranking of alternatives to the MCDA inputs.